Gaining access to critical information - BioMed Central - Neilson, Simon (Septentrio Conference Series, 2014)
BioMed Central advocates free and complete access to scientific research and publishes over 200 fully peer-reviewed open access journals across biology, medicine and chemistry. BioMed Central has decided to take this concept a step further and look into the possibility of access to scientific data and its connectivity with related content. This presentation will talk through BioMed Central's initiatives for open access, including the recent addition of the SpringerOpen journals to its Membership Program. It will also seek to demonstrate how open access can be best adopted by institutions and look at the measures taken by BioMed Central to encourage the wider dissemination of research to the scientific community. Also looking at new and exciting ways of working with scientific data, discussing the benefits enhanced publications can bring to the changing publishing environment.